High-throughput sequencing explores the genetic variability of endophytic bacteria in three Sichuan bamboo species (Phyllostachys edulis, Bambusa rigida, and Pleioblastus amarus) - Yan, Kuan; Li, Xinyi; Cai, Yu; Meng, Lina; Wei, Qin; Zhao, Xianming; M. Y. Heakel, Rania; M. Atif, Amr; A. Abd Elhamid, Mohamed; A. Soaud, Salma; H. El-Sappah, Ahmed (Frontiers in Microbiology, 2025)
IntroductionBamboo is a sustainable and degradable resource for sustenance, high-strength cellulose microfibers, and synthetic fiber in China. Endophytic bacteria enhance root development and ethylene levels, benefiting the host plants’ physiology.MethodsWe investigated the population, diversity, and abundance of endophytic bacteria in the leaves of three bamboo species—Phyllostachys edulis, Bambusa rigida, and Pleioblastus amarus—using high-throughput 16S rDNA sequencing.Results and discussionA total of 1,159 operational taxonomic units (OTUs) were obtained and further classified into 26 phyla, 64 classes, 158 orders, 270 families, 521 genera, and 811 species. The phyla with the highest abundance were Proteobacteria, Actinobacteria, and Myxococcota, and the highest genera included 1,174–901-12, Sphingomonas, and unclassified_f__Enterobacteriaceae. The relative richness of endophytic bacteria in the three species was in the following order: B. rigida > P. amarus > Ph. edulis. The PICRUSt functional richness analysis of endophytic bacteria indicated their involvement in six biological pathways: “cellular processes,” “environmental information processing,” “genetic information processing,” “human diseases,” “metabolism,” and “organic systems.” Among the 41 sub-functions, the most common were “amino acid metabolism,” “carbohydrate metabolism,” “cell motility,” “cellular signaling,” “energy metabolism,” and “membrane transport.” Our results provide precise knowledge for better managing bamboo forests and pave the way for isolating secondary metabolites and potential bioactive compounds.